Preoperative C-Peptide Predicts Weight Gain After Pancreas Transplantation. (June 2020) - Torabi, Julia; Rocca, Juan P.; Kestenbaum, Elizabeth; Ajaimy, Maria; DeFeo, Monica; Konicki, Athena; Liriano-Ward, Luz; Azzi, Yorg; Pynadath, Cindy; Akalin, Enver; Kinkhabwala, Milan; Graham, Jay A.
Background: Transplant recipients are susceptible to cardiovascular complications, obesity, and increased insulin resistance after transplant. Here we assess weight gain in diabetic recipients after pancreas transplantation. Methods: This is a single-center study of 32 simultaneous pancreas and kidney and 5 pancreas after kidney transplant recipients from 2014 to 2018. Starting C-peptide levels ≤ 0.1 ng/mL were used to denote insulin nondetectability (n = 25) and C-peptide levels > 0.1 ng/mL as insulin detectability (n = 12). Hemoglobin A1c, body mass index (BMI), and weight following transplantation were assessed. Results: Hemoglobin A1c at 1 year was 5.9% in the insulin nondetectable recipients and 5.6% in the insulin detectable group ( P = .56). Average BMI after transplant was higher in the insulin detectable group 28.6 versus 24.4 kg/m 2 ( P = .03) despite no difference in starting BMIs (24.9 versus 24.0 kg/m 2, P = .42). The insulin detectable group also had a larger percentage weight change from their starting weight 13.1% versus 0.9 % at 1 year ( P = .02). Linear regression demonstrated that starting C-peptide was a significant predictor of weight gain posttransplant. Conclusions: Patients with elevated C-peptides at time of transplant are susceptible to rapid weight gain postoperatively. These patients may benefit from aggressive nutritional management.